2016
DOI: 10.3389/fmicb.2016.00631
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Significantly Affects the Plaquing and Adsorption Efficiencies of Listeria Phages

Abstract: Listeria-infecting phages are currently being used to control and detect the important foodborne pathogen Listeria monocytogenes; however, the influence of environmental conditions on the interactions between L. monocytogenes and its phages has not been explored in depth. Here, we examined the infective potential of four Listeria phages (two each from the P70-like and P100-like phages of Listeria) against five strains of L. monocytogenes (representing serotypes 1/2a, 1/2b, 4a, and 4b) grown under a range of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 45 publications
5
40
0
Order By: Relevance
“…For instance, the replication of coliphage FRNA at lower than optimal cell growth temperature conditions is slower and can even cease because of the lower expression of F pili and adsorption inhibition (Knolle and Orskov 1967;Woody and Cliver 1995). Similar results have also been reported for phages of Listeria (Tokman et al 2016) and Pseudomonas fluorescens (Sillankorva et al 2004) where incubation at refrigeration temperatures resulted in an increase in the latent period, a reduction in phage burst size and overall lower killing efficacy.…”
Section: Discussionsupporting
confidence: 68%
“…For instance, the replication of coliphage FRNA at lower than optimal cell growth temperature conditions is slower and can even cease because of the lower expression of F pili and adsorption inhibition (Knolle and Orskov 1967;Woody and Cliver 1995). Similar results have also been reported for phages of Listeria (Tokman et al 2016) and Pseudomonas fluorescens (Sillankorva et al 2004) where incubation at refrigeration temperatures resulted in an increase in the latent period, a reduction in phage burst size and overall lower killing efficacy.…”
Section: Discussionsupporting
confidence: 68%
“…Temperature can influences transport through energetic effects on Brownian motion and metabolic activity of motile organisms (Beveridge et al, 2010;Simoncelli et al, 2019). Temperature can also influence encounter through modifications in fluid viscosity, and is a factor influencing virus adsorption rates (Moldovan and Wu, 2007;Tokman et al, 2016). The effects of heterogeneous microenvironments and temperature on microbial predator-prey encounter and capture both require in-depth consideration, which we reserve for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…modification genes on the effect of environmental conditions over nisin efficacy, a non-polar, in-frame deletion mutation of mprF was constructed from the L. monocytogenes 10403S parent strain using the splicing by overlap extension (SOE) method as previously described (Horton et al, 1990;Wiedmann et al, 1998). Additionally, a dltAmprF mutant was constructed by deleting the mprF open reading frame (ORF) from a dltA mutant strain (Tokman et al, 2016) (Wiegand et al, 2008) after a 24 h incubation period at 37 • C, and it is reported in Table 1.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%